BREAST LUMPS AND HISTOPATHOLOGICAL FINDINGS IN A TERTIARY HEALTH FACILITY IN NORTH –CENTRAL NIGERIA: A FIVE YEAR REVIEW - J, Bulus; S, Gidado; I, Pate; F, Golwa; J, Shuai’bu; K, Bangs; B, Dawam (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Breast lumps are common reasons why majority of females irrespective of agepresent to the surgical out-patient departments (SOPD). Breast lumps are either benign ormalignant.A greater percentage of breast lumps that present are benign but breast lumps evokes anxiety andit is important to allay the fears of presenting with breast lumps.Aim: To determine the frequency of breast lumps and their histopathological findingsMaterials and Methods: The study was a five year retrospective review from January,2012 toJanuary,2017 of female patients who presented with breast lump, had excision/biopsy andhistology reports of biopsy samples.Ethical clearance was obtained from the institutional review board. The demographic details,symptom on presentation and histopathology result were documented and analyzed using epiinfo16 versions.